2013
DOI: 10.1007/s11096-012-9748-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of pharmaceutical care to improve health-related quality of life in hemodialysis patients in Iran

Abstract: Providing pharmaceutical care significantly improved HRQoL of hemodialysis patients especially in the role-emotional, mental health, social functioning, and general health dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…In the current study, evaluation of the difference between the group with respect to each domain using independent sample "t" test, it is found that there was a significant improvement in the mean domain score in the intervention group for all the four domains as compared to the group that was not provided with an intervention. This observation is in agreement with similar results obtained at other centers using a variety of QoL questioners [15][16][17][18][19][20]. A significant mean score difference (P < 0.01) is indicative that pharmacists' counseling has an impact on improving the QoL in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, evaluation of the difference between the group with respect to each domain using independent sample "t" test, it is found that there was a significant improvement in the mean domain score in the intervention group for all the four domains as compared to the group that was not provided with an intervention. This observation is in agreement with similar results obtained at other centers using a variety of QoL questioners [15][16][17][18][19][20]. A significant mean score difference (P < 0.01) is indicative that pharmacists' counseling has an impact on improving the QoL in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with written hypertension recommendations had a greater decrease in mean systolic BP (− 11.6 mmHg; p value = 0.035), and BP was controlled in a higher proportion of them (relative risk, 2.14; p value = 0.011) Aspinall et al (2012) USA [ 39 ] Non-randomised controlled study (6 months) Primary care setting, Medical centers To compare the quality of ESA prescribing and monitoring for patients with NDD-CKD in Veterans Affairs Medical Centers with and without pharmacist-managed ESA clinics 572 NDD-CKD patients Pharmacist-Managed ESA Clinic 73.9 (10.9), Usual-Care 78.4 (8.8), Usual Care at ESA Clinic 76.2 (12.0) Dosing and monitoring ESA therapy by pharmacists (n = 314) Usual care at ESA clinic site (n = 91) Usual care (n = 167) More haemoglobin values were in the target range in pharmacist-managed ESA clinics (71.1% vs. 56.9% for usual-care sites; P < 0.001) Veterans in pharmacist-managed ESA clinics had more haemoglobin measurements on average (5.8 vs. 3.6 in usual-care sites and 3.8 in usual care at ESA clinic sites; p = 0.007). Dashti-Khavidaki et al (2013) Iran [ 30 ] Cluster, randomised study (12 months) Haemodialysis ward of a university affiliated tertiary hospital To assess the impact of pharmaceutical care on HRQoL of haemodialysis patients 92 HD patients Intervention 55.4 (15.7), control 48.6 (14.7) Receive clinical pharmacist-led pharmaceutical care in addition to the standard care of the ward as the case group (n = 26) Control group (n = 34) Not reported Via-Sosa et al (2013) Spain [ 18 ] Non-randomised controlled study (9 months) Community pharmacies To evaluate the effectiveness of the community pharmacist intervention in addressing the problem of dosing inadequacy as a consequence of renal impairment in patients over 65 years that were taking 3 or more drugs when compared with usual care 40 community pharmacies 354 CKD patients Intervention 80.8 (7.3), control 82.9 (7.1) Pharmacists used a questionnaire to write a report to GPs detailing the DRPs detected and suggesting changes in therapy. GPs to provide written reply to the pharmacists within 14 days (n = 178) Control group (n = 176) The difference in the prevalence of dosing inadequ...…”
Section: Resultsmentioning
confidence: 99%
“…The majority of processes (often labelled as interventions) included medication chart review to identify any drug-related problems (DRPs) [ 15 31 ]. Many studies reported pharmacists’ interventions in: modifying drug doses and recommending new pharmacotherapy; [ 16 , 19 , 21 – 23 , 25 – 27 , 29 , 30 , 32 40 , 52 , 59 ]; interacting with a member of the multidisciplinary team; [ 15 17 , 19 21 , 23 – 25 , 27 , 31 , 32 , 34 38 , 40 43 ] requesting and monitoring laboratory parameters; [ 15 , 23 , 25 , 27 , 33 , 34 , 36 , 37 , 43 ] assessing appropriateness of medications prescribed for hospitalised patients at each point of care; [ 17 , 22 , 29 , 30 , 35 38 , 40 , 57 ]. Fewer studies described pharmacist processes at out-patient, pharmacist-led clinics relating to the management of specific CKD complications, such as anaemia; [ 34 , 39 , 44 ] hypertension and diabetes; [ 54 ] managing hypertension through telemedicine; [ 41 ] optimising dyslipidaemia management; [ 37 , 45 ] improving haemoglobin A1c levels (HbA1c); [ 43 ] and emphasising smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8]13,[17][18][19][20] There major limitations of the present study that should be addressed include cross-sectional nature of this study and lack of including hospitals which are deprived clinical pharmacy services as a control group and assessing medication errors only in nephrology wards of one hospital that makes it difficult to extrapolate the findings to other wards or the same ward of other institutions. The other limitation is the estimation, but not the exact evaluation of direct medication cost in this study.…”
Section: Discussionmentioning
confidence: 99%